Rapid identification of glycerophospholipids from RAW264.7 cells by UPLC/ESI ‐QTOF‐MS. (8th May 2014) - She, Yuqi; Song, Jianao; Yang, E.; Zhao, Lili; Zhong, Yanmei; Rui, Wen; Feng, Yifan; Wu, Xia
ABSTRACT The study aims to develop a rapid, sensitive ultra‐performance liquid chromatography coupled with an electrospray ionization quadruple time‐of‐flight tandem mass spectrometry (UPLC/Q‐TOF‐MS) analytical method for identifying glycerophospholipids (GPLs) from RAW264.7 cells. A total of 78 GPLs including 22 phosphatidylethanolamines (PEs), 49 phosphatidylcholines (PCs), four phosphatidylglycerols, one phosphatidylinositol and two unknown GPLs were identified. PC (14:0/16:1), PC (14:0/16:0), PE (0:0/20:3), PE (22:5/0:0) and PE (22:3/0:0) were identified for the first time. The UPLC/Q‐TOF‐MS method is suitable for targeting analysis of GPLs from RAW264.7 cells, which allows us to find out new GPLs compositions related to inflammatory diseases and to explain their pharmacological roles in inflammatory process. Copyright © 2014 John Wiley & Sons, Ltd.